miR-202 Mediates Metabolic Shift in Lung Cancer Cells via Targeting HK2 - Li, Jin; Zhang, Baohua; Chen, Qihuang; Li, Qiang (Current Signal Transduction Therapy, 2014)
Cancer cell metabolism plays an important role in the progression of lung cancer. It is characterized through a shift from an oxidative to a glycolytic bioenergetics pathway, a phenomenon referred to as the warburg effect. However, the deregulation of miRNAs contributing to the warburg effect and to cancer cell metabolism is still unknown. In the present study, the results demonstrate that the expression of miR-202 is significantly decreased, and it induces a metabolic shift in lung cancer cells. miR-202 exerts this function through targeting HK2, resulting in the increase of glucose uptake and lactate production. The altered metabolism induced by miR-202 leads to cancer cell growth. These studies demonstrated that miR-202 may be involved in the metabolic shift via targeting HK2 in lung cancer cells.
Keywords: lung cancer